Effect of recombinant factor VIIa on the hemostatic defect in dogs with hemophilia A, hemophilia B, and von Willebrand disease. - Brinkhous, K M (1989)
Recombinant factor VIIa (rF.VIIa) is a two-chain procoagulant enzyme (Mr, approximately 50,000) active only when complexed with tissue factor in the extrinsic clotting system. We administered human rF.VIIa to hemophilic and von Willebrand disease (vWD) dogs to determine its hemostatic effectiveness and survival in the circulation. Hemophilia A dogs lacking factor VIII demonstrated an immediate increase in plasma rF. VIIa and prompt stoppage of hemorrhage at bleeding time (BT) sites. In seven studies in two dogs, the range of dose of rF. VIIa was 50-220 micrograms/kg, with an apparent 7- to 11-fold increase in plasma factor VII and a mean recovery in plasma of 34%. The t1/2 was 2.8 +/- 0.5 hr. The BT was normalized except in an animal given the minimum dose. In four studies in two hemophilia B dogs lacking factor IX, BT was normalized. The elevation in plasma factor VII was by a factor of 8-30, with a mean recovery of rF.VIIa in plasma of 44%. In two studies in a homozygous vWD dog lacking von Willebrand factor, which is needed for platelet function, BT was not corrected even though large doses of rF. VIIa were given. The human rF. VIIa protein was immunogenic for dogs. These studies indicate that factor VIIa corrects the hemostatic defect in dogs with hemophilia A and B, diseases primarily of the intrinsic clotting system, but does not correct the hemostatic defect in vWD.